UNDERSTANDING THE IMPACT OF TRAVEL WEBSITES EFFECTIVENESS CHARACTERISTICS ON EXTRINSIC & INTRINSIC MOTIVATIONS OF TRAVEL WEBSITES ADOPTION: MALAYSIAN TRAVELLERS' PERSPECTIVE - NORZALITA ABD AZIZ (ASEAN Journal on Hospitality and Tourism, 2008)
There is growing reliance on the websites for promotion of tourism and travel related product/services. Thus, identification of travel web site effectiveness attributes based on potential travellers/internet users ' expectation is necessary. This paper explores the web travel effectiveness attributes and their relationships with the intrinsic and extrinsic motivation of Malaysian travellers. Here an attempt is made in the context of explaining internet users ' beliefs using Technology Acceptance Model with data collected from 679 internet users/travellers. Factor analysis results indicate three dimensions of travel web effectiveness were derived, namely: i) technical adequacy & customization,ii) system quality & specific content and iii) web appearance. In testing the model, multiple regression results show that the above dimensions have positive influence on individual extrinsic motivation (perceived usefulness). Meanwhile, web appearance and technical adequacy & customization have positive influence on intrinsic motivation (perceived ease of use and enjoyment) of travel websites.